A constituição social dos homens : contribuições da história, ciências sociais e psicanálise - Piovezan, Vinícius Borges (2022)
The theme of masculinities and men as socially constituted beings is relatively recent. It arises around the sixties and seventies as a result of effervescence of the so-called secondwave feminist movement. The emergence of such a theme has been increasingly necessary as men are summoned to think about the status they occupy in society and, consequently, about how these positions and models are maintained regarding the socialization of the new members of a culture. The research is of a theoretical-conceptual nature and focuses on the social constitution of men, especially from the notion of socialization of the psychoanalyst Cornelius Castoriadis. Supported by a psychoanalytic theoretical-methodological contribution and criticism of the metaphysics of presence, the investigation was undertaken below the traditional molds of doing research and the prior elaboration of objectives and steps to be followed in order to achieve them; that is, like an adventure that is known where it starts from without knowing in advance where this adventure can take us. Along with this epistemological assumption, we start from the conception that, at first, subject-researcher and object-of-research are intertwined and that the differentiation between one and the other is already an effect of the investigative process. Assuming these assumptions, the question about the social constitution of men and their particularities were examined in four areas. Firstly, from its emergence as an academic debate, in order to present the questions and formulations that were in dispute. Subsequently, from the difficulties and implications that permeate the central terms for this investigation and from a mapping of the discursive constellations that accompany, in the texts consulted, the notions of man, virility and masculinity. Thirdly, we present the values, sociabilities and sensitivities linked to the notion of cis-heterosexual man in an aspect of the history of Western civilization, at first from the signifier of andréia in Ancient Greece, and then from the signifier of virility Rome, in the Medieval period and in the Enlightenment. We present how in each of these periods the characteristics that qualify an individual as a man are contingent on them. Finally, we address the process of socialization supported by a psychoanalytic theoretical framework, and, therefore, focusing on its psychic dimension. This study is part of the research line “Clinical processes and sociocultural contexts” of the Postgraduate course Program in Psychology contexts" of the Postgraduate Program in Psychology of the Federal University of Mato Grosso.